Education for the Future: Critical Analysis of the Education for Sustainable Development (ESD) Programs in Learning - Sutrio Sutrio; Ahmad Busyairi; Muhammad Zuhdi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Environmental problems have now become a global issue faced by almost all countries, including Indonesia. One joint effort to overcome environmental problems is through the education sector called Education for Sustainable Development (ESD). This research aims to analyze research trends and good practices regarding implementing ESD in the learning process at schools or universities through a systematic literature review study. A total of 29 from 576 research articles discussing the integration of ESD in learning were analyzed in this research. Articles were collected using the Publish or Perish application with the Scopus and Google Scholar databases. The results of the analysis show that the learning approach is student-centered, uses a variety of methods, utilizes the latest technology, is collaborative, holistic, creates sustainable values; and is oriented towards developing local potential is a recommended learning design in implementing ESD effectively. Challenges such as limited human resources in schools or universities that understand the concept of ESD integration in learning are still the main obstacles to implementing ESD in classroom learning. These findings are expected to provide a significant contribution to the development of relevant and future-oriented education.